Understanding of Pathophysiological Basis of Feeding Intolerance in Critically ill Children - Soyhan Bağcı; Elif Keleş Gülnerman; Andreas Müller (Cam & Sakura Medical Journal, 2021)
Children with critical illnesses are at increased risk for intestinal injury, gastrointestinal dysfunction, and feeding intolerance, which are associated with delayed recovery and increased morbidity and mortality during their course in the pediatric intensive care unit (PICU). Optimizing energy and protein delivery significantly reduces the incidence of infectious complications and multiorgan failure in critical illness. Enteral nutrition (EN) is the preferred mode of nutrient intake in patients with critical illnesses. Despite the growing awareness of the benefits of EN in patients with critical illnesses, subsequent maintenance of EN delivery in PICUs remains suboptimal. In children with critical illnesses, little data are reported on the factors that influenced EN. Feeding intolerance in children with critical illnesses may be due to alterations in gastrointestinal motility secondary to underlying disease or medication administration. This study aimed to summarize recent insights into the role of hyperglycemia, EN caloric density, and gastrointestinal feedback mechanism, and routine intensive care management, such as sedation, analgesia, and catecholamine on feeding intolerance in children with critical illnesses.